Assessing Scottish tax strategy and policy - Stuart Adam; David Phillips (Institute for Fiscal Studies (IFS), 2025)
The Scottish Government has a range of tax powers at its disposal, which it has used in recent years to forge an increasingly distinct tax policy from the rest of the UK. In its 2025-26 Budget, the Scottish Government made a number of tax policy changes, including to income tax, business rates, and land and buildings transaction tax (LBTT). Alongside the Budget, the Scottish Government also published a Tax Strategy, setting out its approach to tax policymaking and evaluation and a number of priorities for tax policy and administration. Only the income tax changes were clearly linked to the new Tax Strategy. This chapter of our report assesses the Scottish Government's Tax Strategy and tax policy in turn; the next chapter looks in depth at one tax particularly ripe for reform - council tax.
Keywords: 330; Taxes and benefits; Devolved government finances; Income taxes; Property taxes; Scotland; Tax; Tax administration; Taxes on wealth and spending